Causes of variation orders in construction projects in the Gaza Strip - Enshassi, Adnan; Arain, Faisal; Al-Raee, Sadi (Journal of Civil Engineering and Management, 2010)
The maximum project performance would be achieved if the work invariably flows smoothly within time limits and anticipated budget. Variation orders result in time delay, cost overrun, quality defects, and other negative impacts. This is common in construction projects in Gaza Strip. The main objective of this study was to analyze the causes of variation orders in construction projects in Gaza Strip. The causes of variation orders in construction process in Gaza Strip were investigated through questionnaire survey of 36 classified construction companies, 25 consultants and 15 owners. 64 causes of variation orders were identified from literature review. The study results identified the top ten most important factors that include lack of materials and equipment spare parts due to closure, change in design by consultant, lack of consultant's knowledge of available materials, errors and omission in design, conflicts between contract documents, owner's financial problems, lack of coordination among project parties, using inadequate specification for local markets by international consultant, internal politics, and change is specification by owners. In general, the study shows an agreement among owners, consultants and contractors regarding the ranking of the 64 factors causing variation orders. The results al‐so reveal that factors related to consultant are the most important causes of variation orders followed by the factors related to owner. An understanding of the causes of variation orders would be helpful for building professionals in assessing variation orders. Furthermore, the study would also assist professionals in taking proactive measures for reducing variation orders in construction projects. The findings from this study would also be valuable for all construction professionals in general.First Published Online: 10 Feb 2011